2017
DOI: 10.1111/twec.12485
|View full text |Cite
|
Sign up to set email alerts
|

Are bilateral and multilateral aid‐for‐trade complementary?

Abstract: Using the first comprehensive estimates of ad valorem tariff equivalent bilateral trade costs spanning the time period 2002–10, we examine whether the aid‐for‐trade (AFT) inflows reduce bilateral trade costs facing aid recipients. If so, we ask whether the trade costs reduction effects of AFT from bilateral and multilateral sources are complementary. By showing the extent to which the observed trade cost reduction effects of AFT from bilateral (multilateral) sources correlate with the magnitudes of AFT disburs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“… Some researchers have shown AfT reduce the trade costs facing aid recipients (e.g. Tadesse, Shukralla, & Fayissa, ). Some other researchers have assessed how the AfT has been allocated (e.g.…”
mentioning
confidence: 99%
“… Some researchers have shown AfT reduce the trade costs facing aid recipients (e.g. Tadesse, Shukralla, & Fayissa, ). Some other researchers have assessed how the AfT has been allocated (e.g.…”
mentioning
confidence: 99%
“…The reviewed empirical studies have shown that the same category of AfT inflows may produce different effects according to the geographical region, to which the disbursements are directed. Tadesse et al (2017) observed the statistically significant reduction in bilateral trade cost by AFT in all regions except for the Pacific region; the finding proves that the degree of effectiveness varies from one region to another. For instance, the greatest influence was observed in Europe (−0.038), followed by the USA (−0.024) and Asia (−0.017); the poorest impact was observed in Africa (−0.007).…”
Section: Discussion and Findingsmentioning
confidence: 59%
“…In addition, few studies have looked at the impacts of AfT in various geographical regions. For instance, Tadesse et al (2017) differentiated the countries into sub-categories: African countries; Pacific region countries; European countries; American countries; and Asian countries. Similarly, Ly-My et al (2020) focused on six sub-categories of recipient countries: Europe and Central Asia (14 countries); East Asia and Pacific (12 countries); Middle East and North Africa (13 countries); South Asia (5 countries); SSA (35 countries); and Latin America and the Caribbean (25 countries).…”
Section: Discussion and Findingsmentioning
confidence: 99%
See 2 more Smart Citations